Do public subsidies add to private sector R&D activity? Microeconometric evidence for regional innovation policy in East Germany - Janina Reinkowski; Timo Mitze; Björn Alecke; Gerhard Untiedt (European Regional Science Association (ERSA), 2010)
We analyse the effect of public Research and Development (R&D) subsidies on private sector innovativeness for a cross-section of East German firms applying different matching estimations, which are primary based on an estimate of a propensity score. To do so, we use a until now unexplored representative database for the federal state of Thuringia covering around 1500 firm and the period 2001 to 2003. From a methodological perspective we apply a two-step microeconometric policy evaluation approach that estimates a probit equation for R&D programme participation in a first step and then uses the fitted values (the so called propensity score) in a second step matching approach. Here we compare the outcome difference of subsidized and non-subsidized firms for a broad set of private sector R&D variables such as general patenting activity, total number of patents, R&D expenditure and employment as well as R&D intensity (defined as R&D expenditures relative to total turnover). Our empirical results indicate that the treated firms indeed show a significantly higher research activity measured in terms of R&D intensity and patent application. With respect to R&D intensity for instance this difference is estimated to vary between 4 to 5 percentage points. Our findings thus give support to earlier evidence for East Germany, which so far have been solely based on the Mannheim Innovation Panel (MIP) as the only database accessible for analyses on the role of public policy in the innovation process of German firms. Our empirical results for Thuringia pass a variety of robustness checks based on different estimation routines (Kernel, Mahalanobis distance) and additional matching criteria beyond the propensity score (such as same industry code as well as size group). We also perform sensitivity checks for subgroups of the sample, e.g. we include only those firms who regularly engage in R&D activity. All results hint at the positive stimulus given by public R&D subsidies to enhance the private sector innovativeness.
Keywords: H25; H54; C14; C21; 330; Propensity Score Matching; R&D Subsidies; East Germany